2017
DOI: 10.1186/s12879-017-2835-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of sexually transmitted pathogens and Human Papillomavirus in cervical samples of women of Brazil

Abstract: BackgroundSome sexually transmitted infectious agents, such as Chlamydia trachomatis and Herpes simplex, cause local inflammation, and could contribute to Human Papillomavirus (HPV) and cervical lesion progression. Thus, the aim of this study was to determine any association between the presence of microorganisms of gynecological importance, sexual behavior, clinical and demographical variables to the development and progress of cervical lesions.MethodsOne hundred and thirty-two women between 14 and 78 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
3
26
0
3
Order By: Relevance
“…These data are consistent with previous studies,27 in which G. vaginalis was detected in 91.9% of women with cervical lesions in addition to a positive association with the presence of injury, indicating a higher detection in women with high-grade squamous intraepithelial lesions. In another study, a positive association was found between the presence of G. vaginalis and cervical injury 28.…”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with previous studies,27 in which G. vaginalis was detected in 91.9% of women with cervical lesions in addition to a positive association with the presence of injury, indicating a higher detection in women with high-grade squamous intraepithelial lesions. In another study, a positive association was found between the presence of G. vaginalis and cervical injury 28.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, the Ureaplasma parvum and their related taxa manifested higher richness in the baseline HPV-positive group compared with the baseline HPVnegative group. This is consistent with previous studies in different populations of the world indicating that Ureaplasma parvum was associated with a significantly increased risk of overall HPV infection and increased risk of abnormal cervical cytopathology (20)(21)(22). It was reported that the infection of Ureaplasma could lead to scarring and damage of the epithelium (23), suggesting that infection of the reproductive tract with Ureaplasma parvum might also increase the risk of HPV infection by facilitating viral infections.…”
Section: Discussionsupporting
confidence: 91%
“…However, several recent studies investigating the role of cervical co-infections of Ureaplasma spp. and other STIs in association with hrHPV, have supposed that these could be possible cofactors interacting with HPV in the development of precancerous and cancerous cervical lesions [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…To date, nearly 200 different HPV types have been identified, including twelve classified by the International Agency for Research on Cancer (IARC) as oncogenic or "high-risk" HPV types (hrHPV 16,18,31,33,35,39,45,51,52, 56, 58 and 59) [2]. Although most HPV infections are benign, persistent infection with one of the carcinogenic hrHPV types is a well-established necessary cause of cervical cancer [3].…”
Section: Introductionmentioning
confidence: 99%